Transformation of Economic Structure and Changes of Labor Proportion in East Java Province 1998-2012 - Herdianti, Yulia Maris; Burhan, M. Umar; Pratomo, Devanto Shasta (International Journal of Social and Local Economic Governance, 2015)
The transformation of economic structure is not only act as a sector dominance contributing to Gross Regional Domestic Product, but also acts as the dominance of labor sector absorption. In 1994, the dominance of primary sector in contributing East Java’s Gross Regional Domestic Product is already replaced by secondary sector and later by tertiary sector in 2004. The labor sector absorption is still dominated by agricultural sector until now. This research was aimed to describe the patterns of Transformation of economic structure and changes in the proportion of labor in East Java Province from 1998 to 2012, as well as analyzed the effect of each variables. By using factor analysis for latent variables first, the quantitative result based on path analysis has proved that economic growth and income per capita has a direct effect to the Transformation of economic structure. The increase of economic growth and income per capita has lead to the decrease in agricultural (primary sector) and industrial (secondary sector) proportion in contributing East Java’s GRDP which is followed by the increase proportion in trade, hotel and restaurant (tertiary sector). The Transformation of economic structure has a direct effect to change the proportion of labor, whereas the economic growth and income per capita have indirect effect to that. During this process, the agricultural labor absorption decreased very slowly while industrial labor absorption increased slowly, as well as the trade, hotels and restaurants. The results also showed that the changes in the the proportion of labor has direct effect to income per capita along with the domination of high productivity sector such as trade, hotels and restaurants which leads the economic growth.Keywords : Transformation of economic structure, changes of the proportion of labor, economic growth, income per capita